Neuro-psycho-education-existential group program: Evidence based Professional Practice at persons with psychiatric and intellectual disabilities. - Ndoja, Suela (European Journal of Sustainable Development, 2013)
Aim:to describe the impact of neuro-psycho-education-existential group program onpersonal formation and its possible application for mental health, health and socialprofessions in different contexts by taking into consideration the current practice withpsychiatric and intellectual disability persons.Framework: the theoretical foundations of clinically based in combination ofperspectives as neuropsychology, psycho education and existentialism are reviewed andthe common positive elements of practice are identified.Practical application:examples of well-defined ten weekly neuro-psycho-education-existential interventions in group developedin public spaces are presented that meetcriteria for empiricallysupported psychologicalinterventions at persons with psychiatricand intellectual disabilities.Outcomes:in conclusion, the specific application of neuro-psycho-education-existentialgroup program for health care, mental healthand social practice at both the clinical andcommunity disability level is discussed.Implications:the need for further evaluation and design research is consideredfor abetter implementation into practice.